The Effect of the Mahasiswa Mengaji Program on the Qur’an Reading Skills of IAIN Curup Students - Warsah, Idi; Morganna, Ruly (Institut Agama Islam Negeri (IAIN) Curup, 2025)
In response to growing concerns about the decline of Qur’anic literacy among university students, this mixed-methods study examined both the measurable improvements in reading proficiency resulting from the Mahasiswa Mengaji program—an initiative of the Rector at the State Islamic Institute of Curup (IAIN Curup)—and the contextual factors that facilitated these improvements. A total of 500 students participated in a pre-experimental one-group pretest–posttest design, with their Qur’anic reading skills assessed across phonological accuracy, reading fluency, and tajwīd application. Ten participants were purposively selected for in-depth interviews, analyzed using the interactive model, to explore the underlying supports that influenced these outcomes. Quantitative findings showed significant gains in all domains: phonological accuracy (t = 31.276, p < 0.001), reading fluency (t = 40.842, p < 0.001), and tajwīd application (t = 39.525, p < 0.001), confirming the program’s effectiveness in enhancing Qur’anic reading. Complementing this, qualitative results identified eight key enabling supports, namely self-regulated learning, teacher scaffolding and presence, peer support, family motivation, internal drive, accessible learning resources, and consistent practice, that explain the mechanisms behind the observed improvements. Taken together, the integration of statistical evidence and thematic insights demonstrates how the program functions not only as an effective intervention but also as a holistic educational strategy for strengthening Qur’anic reading skills.